Peran Alun-alun Desa Drajat Sebagai Ruang Terbuka Publik dalam Mendukung Pertumbuhan Ekonomi Pedagang Kecil - Abdillah, Fahad (At-Tasharruf "Jurnal Kajian Ekonomi dan Bisnis Syariah", 2024)
This study examines the role of Alun-alun Desa Drajat as a public open space and its contribution to the economic growth of small vendors. Located in Paciran District, Lamongan Regency, this town square serves as a center for social and economic activities for the community. Besides functioning as a recreational area, the square also supports the local economy through the presence of small vendors offering various products. This research employs qualitative methods, including observation and interviews. Results indicate that strategic location, product diversity, affordable pricing, and local government support contribute to the economic growth of small vendors. The town square plays a significant role in increasing vendor income and strengthening social bonds within the community. This underscores the importance of optimal management of public open spaces to support local economies. Penelitian ini membahas peran Alun-alun Desa Drajat sebagai ruang terbuka publik dan kontribusinya terhadap pertumbuhan ekonomi pedagang kecil. Terletak di Kecamatan Paciran, Kabupaten Lamongan, alun-alun ini menjadi pusat kegiatan sosial dan ekonomi bagi warga. Selain berfungsi sebagai tempat rekreasi, alun-alun ini juga mendukung perekonomian lokal melalui keberadaan pedagang kecil yang menawarkan berbagai produk. Penelitian ini menggunakan metode kualitatif dengan observasi dan wawancara. Hasilnya menunjukkan bahwa faktor lokasi strategis, keragaman produk, harga terjangkau, dan dukungan pemerintah lokal mendorong pertumbuhan ekonomi pedagang kecil. Alun-alun berperan signifikan dalam meningkatkan pendapatan pedagang serta memperkuat ikatan sosial masyarakat. Hal ini menegaskan pentingnya pengelolaan ruang terbuka publik yang optimal guna mendukung ekonomi lokal.